2010
DOI: 10.1016/j.mito.2010.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and the degradation of mitochondria

Abstract: The cellular process of macromolecular degradation known as macroautophagy has long been known to play a role in the elimination of mitochondria. Over the past decade, much progress has been made in the development of systems by which the nature and mechanism of mitochondria degradation may be studied. Recent findings imply that the degradation of mitochondria via autophagy may be more specific and more tightly regulated than originally thought, and have led to designation of this specific type of autophagy as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(93 citation statements)
references
References 77 publications
(82 reference statements)
1
91
0
1
Order By: Relevance
“…Recruitment of Parkin was followed by removal of these damaged mitochondria through a specialized form of autophagy known as mitophagy, in which mitochondria are specifically degraded following engulfment by autophagosomes (for review, see Goldman et al 2010). Recent findings suggest that mitophagy is intimately linked with changes in mitochondrial size and shape brought about through fission and fusion (for review, see Hyde et al 2010).…”
Section: Pink1 and Parkin Promote Mitophagymentioning
confidence: 99%
“…Recruitment of Parkin was followed by removal of these damaged mitochondria through a specialized form of autophagy known as mitophagy, in which mitochondria are specifically degraded following engulfment by autophagosomes (for review, see Goldman et al 2010). Recent findings suggest that mitophagy is intimately linked with changes in mitochondrial size and shape brought about through fission and fusion (for review, see Hyde et al 2010).…”
Section: Pink1 and Parkin Promote Mitophagymentioning
confidence: 99%
“…Therefore, it was suggested that the two proteins could act in common pathways, with parkin working downstream of PINK1, since transgenic expression of parkin rescued all PINK1 impairments, but not the contrary [243,250,251]. Goldman et al(2010) [252], described that PINK1 and parkin both display a role in the mitochondrial targeting of autophagy, a process by which the cells degrade intracellular material through lysosomes. Mitophagy, which is the mitochondrialͲ specific form of this process, is important in the control of damaged or stressed cellular organelles.…”
Section: Ptenǧinduced Putative Kinase 1 (Pink1)mentioning
confidence: 99%
“…Maintenance mitophagy serves to keep a healthy pool of mitochondria by clearing aging mitochondria. 10 While the specific signals that initiate autophagic clearance of mitochondria are still being fully described, loss of mitochondrial membrane potential appears to be strongly associated with removal by mitophagy.…”
Section: Introductionmentioning
confidence: 99%